2013
DOI: 10.1017/s0959774313000498
|View full text |Cite
|
Sign up to set email alerts
|

The Materiality of Rock Art and Quartz: a Case Study from Mpumalanga Province, South Africa

Abstract: A San rock-art site in northeastern South Africa includes several intriguing features, including rubbed patches of pigment and a red line painted on top of a quartz vein. This article interrogates the relationships between hunter-gatherer beliefs, materiality and rock paintings, and suggests that San painters and viewers engaged with the unique Mpumalangan site for specific ritualistic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Ethnographic and ethnohistoric records reveal that quartz was and is considered an important animistic agent, in the sense that quartz did and does things; in many hunter-gatherer worldviews, quartz is a potent agent (Pearson 2002;Hampson 2013). Indeed, a study of quartz from a dual and intertwined functionalist and symbolic perspective-that is, by examining concepts of materiality in addition to raw materials (Tilley 2004;Ingold 2007)helps break down rigid, but rarely scrutinised Western divisions such as animate:inanimate and nature:culture.…”
Section: Ethnohistorymentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographic and ethnohistoric records reveal that quartz was and is considered an important animistic agent, in the sense that quartz did and does things; in many hunter-gatherer worldviews, quartz is a potent agent (Pearson 2002;Hampson 2013). Indeed, a study of quartz from a dual and intertwined functionalist and symbolic perspective-that is, by examining concepts of materiality in addition to raw materials (Tilley 2004;Ingold 2007)helps break down rigid, but rarely scrutinised Western divisions such as animate:inanimate and nature:culture.…”
Section: Ethnohistorymentioning
confidence: 99%
“…Lemaitre (2012: 24) concludes that “it is therefore possible that this crystalline particularity possesses an intrinsic value”. In addition, Hampson (2013) has shown that quartz veins form important components at South African rock art sites; one example in Mpumalanga province includes red pigment carefully and directly applied to a quartz seam.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Whitley et al (1999) have shown that quartz hammerstones were carefully selected and used over a long period for ritualistic reasons. From a purely technical viewpoint, quartz is not the best stone for repeated percussion, but, as we know from research elsewhere (Hampson 2013b), it is considered potent by many indigenous groups.…”
Section: ) Vulvas and Cupulesmentioning
confidence: 99%
“…Lewis-Williams 1981; Huffman 1983; Yates et al . 1985; Dowson 1992; Smits 1993; Deacon 1994; Walker 1996; Hollmann 2002; Blundell 2004; Lewis-Williams & Pearce 2004a; Mguni 2004; Smith & Ouzman 2004; Challis 2005; Deacon & Foster 2005; Eastwood & Eastwood 2006; Loubser 2006; Wright & Mazel 2007; Mazel 2009; Lewis-Williams & Challis 2011; Hampson 2013). Certain researchers argue that some distinctive San rock art, largely in the northern parts of the subcontinent, also deals with the initiation of girls at puberty into womanhood (Eastwood & Eastwood 2006; Hollmann 2013).…”
mentioning
confidence: 99%